Combined use of non-steroidal anti-inflammatory drugs and symptomatic slow-acting drugs in musculoskeletal diseases - A. E. Karateev; A. M. Lila; V. A. Parfenov; M. N. Khokhlova; M. A. Strakhov (Современная ревматология, 2023)
Musculoskeletal diseases, such as osteoarthritis (OA), nonspecific back pain (NBP), and periarticular soft tissue pathology (PSTP – tendinitis, enthesitis, bursitis, etc.) are one of the most common reasons for visiting general practitioners. The treatment of this pathology is based on the complex use of drugs and non-drug methods for maximum pain control and lost function restoration. Considering the common pathogenesis of musculoskeletal pain in OA, NBP, and PSTP, it is advisable to base the therapy of these diseases on a single algorithm. Of course, when prescribing treatment, one should take into account "red flags" (symptoms of life threatening diseases), features of the clinical course, patient's psycho-emotional condition, and comorbid diseases.Development of a unified tactic for the treatment of musculoskeletal pain will significantly reduce the time spent on a diagnostic search and the choice of adequate therapy, which will facilitate the work of a general practitioner. Thus, non-drug approaches (patient education, kinesiotherapy, psychotherapeutic methods, etc.), non-steroidal anti-inflammatory drugs (NSAIDs) and symptomatic slow-acting drugs (SYSADOA) seem to be the most rational approach in the debut of the treatment of OA, NBP and PSTP. Among NSAIDs, celecoxib seems to be one of the optimal drugs in terms of efficacy and safety, and among SYSADOAs – diacerein. There is evidence that the combined use of these drugs may increase their analgesic and anti-inflammatory potential.